"'Organics' are good, but we don't know exactly what the term means!" Trust and Knowledge in Organic Consumption. (1st October 2016) - Thorsøe, Martin Hvarregaard; Christensen, Tove; Povlsen, Karen Klitgaard
Abstract : This article explores consumer trust in organics and investigates the relationship between credibility, trust, and knowledge in a mixed-method study incorporating a survey, a focus group, and individual interviews. Danish consumers show a high level of systemic trust in the organic label, which can be trumped by personal trust. Consumers wanting to know more about organics are mainly those who already know a lot, while others show a deliberate lack of knowledge. Furthermore, it is argued that knowledge does not lead to trust—trust replaces knowledge, and consumers largely seek confirmation of their views when they have already made up their minds about organics.